I-CAN: Information-Centric Future Mobile and Wireless Access Networks - Polyzos, George; Siris, Vasilios; Xylomenos, George; Marias, Giannis; Toumpis, Stavros (EAI Endorsed Transactions on Cloud Systems, 2014)
This short paper describes the objectives and initial results of project I-CAN: Information-Centric Future Mobile and Wireless Access Networks. I-CAN seeks to radically advance the integration of cellular and wireless access technologies by developing and evaluating architectures and procedures for future access networks based on Information-Centric Networking (ICN).
Keywords: future internet; heterogeneous wireless access; integration of mobile and wireless networks